The murder of George Floyd and the mediatization of solidarity by top-ranked universities. (2nd November 2021) - Stack, Michelle
ABSTRACT: This paper is a critical discourse analysis of the responses by Harvard and Oxford to the murder of George Floyd. Findings point to how the two institutions visually separate stated commitments to equity and their identities as world-class institutions. The official university response is compared and contrasted to student media, The New York Times and The Guardian. Mediatization provides a framework for looking at the multiple logics that elite universities are responding to in maintaining their top-ranked identities while also responding to media pressure to acknowledge racism in their institutions.